Pengaruh Kualitas Pelayanan Islami terhadap Kepuasan Nasabah Bank Syariah Bukopin Kcp Gresik - Perdana, Ryan Wahyu; Fahrullah, Arasy (Universitas Negeri Surabaya, 2020)
Increasing customer satisfaction is a necessity for Islamic banking, given the increasingly fierce competition in the financial services business. Customer satisfaction can maintain the existence of Islamic banking. One of the instruments that can increase customer satisfaction is to provide quality services. This study aims to determine the effect of the quality of Islamic banking services on customer satisfaction. This type of research is a quantitative study consisting of independent variables Islamic service quality using indicators of physical evidence, reliability, responsiveness, assurance, empathy, and sharia compliance. Data collection techniques using accidental sampling with a total of 100 respondents. Data is processed using simple regression method. The results of this study are the quality of Islamic service influences customer satisfaction which means that 21.4% of customer satisfaction variables can be explained by Islamic service quality variables